A clinical case of peripheral ameloblastoma - Carolina Cavaliéri Gomes (Brazilian Journal of Oral Sciences, 2016)
The peripheral ameloblastoma (PA) is a rare, benign, extraosseous odontogenic soft tissue tumour that is confined to the gingiva or alveolar mucosa. The PA presents the same histological characteristics of intraosseous ameloblastoma, although it is less aggressive than this classical subtype. We report a clinical case of PA of the alveolar mucosa in the right posterior maxilla, highlighting the importance of histological examination to the diagnosis.